Peripheral vestibular system involvement in multiple sclerosis and associations with the disease severity - Aydın Cantürk, İlknur; Mutlu, Berna Özge; Yılmaz, O?uz; Bayazıt, Yıldırım Ahmet (Karger, 2023)
Introduction: Multiple sclerosis (MS) is an autoimmune disease that can affect balance, gait, and improve fall risk. The aim of this study was to investigate peripheral vestibular system involvement in MS and associations with the disease severity. Methods: Thirty-five adult patients with MS and 14 age- and gender-matched healthy controls were evaluated using video head impulse test (v-HIT), cervical vestibular evoked myogenic potential (c-VEMP), ocular vestibular evoked myogenic potentials (o-VEMPs), and sensory organization test (SOT) of computerized dynamic posturography (CDP). The results of both groups were compared, and association with EDSS scores was evaluated. Results: There was no significant difference between the groups regarding v-HIT and c-VEMP results (p > 0.05). There was no association of the v-HIT, c-VEMP, and o-VEMP results with EDSS scores (p > 0.05). There was no significant difference between the o-VEMP results of the groups (p > 0.05) except for N1-P1 amplitudes (p = 0.01). The amplitudes of N1-P1 were significantly lower in the patients compared to controls (p = 0.01). There was no significant difference between the SOT results of the groups (p > 0.05). However, significant differences were found within and between groups when the patients were categorized according to their EDSS scores with a cutoff point of 3 (p < 0.05). There were negative correlations between the EDSS scores and composite (r = -396, p = 0.02) and somatosensory (SOM) scores (r = -487, p = 0.04) of CDP in the MS group. Conclusion: Although central and peripheral balance-related systems are affected in MS, the impact of disease on the peripheral vestibular end organ is subtle. In particular, the v-HIT, which was mentioned previously as a detector of brainstem dysfunction could not be a reliable tool in the detection of brainstem pathologies in MS patients. The o-VEMP amplitudes may be affected in the early stages of the disease, possibly due to the crossed ventral tegmental tract, oculomotor nuclei, or interstitial nucleus of Cajal involvements. An EDSS score >3 seems a cutoff level indicating abnormalities in balance integration.
Keywords: Computerized Dynamic Posturography; Multiple Sclerosis; Vestibular Evoked Myogenic Potentials; Video Head Impulse Test